THE CENTRAL ASIAN TIGER: EXPORT SPECIALIZATION IN UZBEKISTAN: OPPORTUNITIES FOR ECONOMIC DIVERSIFICATION AND DEVELOPMENT - Stephens, Aaron R; Tajekeev, Ziynatdin (The European Journal of Applied Economics, 2023)
As expansion along the Silk Road is flourishing this research examines export specialization in Uzbekistan through a time series analysis of RCA and RSCA with a discussion on how export diversification has led to economic development since 2017. International trade in Uzbekistan and the region of Central Asia is first explored through history before the most recent data is examined. Specialized sectors (silk, cotton, edible fruits and vegetables, copper, etc.) are explored through the analysis, policy initiatives, and extant literature within a comprehensive discussion. Finally, policy recommendations are provided. This research is the first to explore export specialization in Uzbekistan through RCA and RSCA. It highlights the efforts of the current Uzbek administration to diversify and develop its economy by harnessing the power of international trade. Other Central Asian and developing economies could learn from this case.